Access over 20 million homework & study documents
search

2 11 x 31 xsolution multiply by 1 x

Content type

User Generated

Rating

Showing Page:
1/1
-2 = 1/1+x - 3/1-x
Solution
multiply by (1-x)(1+x) on both sides -2(1-
x)(1+x) = (1-x) - 3(1+x) 1-x - 3(1+x) = -2(1-x^2) 2x^2 + 4x
=0 2x(x+2) = 0 x(x+2) =0 x=0,-2

Sign up to view the full document!

lock_open Sign Up

Unformatted Attachment Preview

-2 = 1/1+x - 3/1-x Solution multiply by (1-x)(1+x) on both sides -2(1x)(1+x) = (1-x) - 3(1+x) 1-x - 3(1+x) = -2(1-x^2) 2x^2 + 4x =0 2x(x+2) = 0 x(x+2) =0 x=0, -2 Name: Description: ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

Anonymous
Really useful study material!

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4